Physical fitness measures of cadet wrestlers - Mirzaei, B.; Curby, D. G.; Barbas, I.; Lotfi, N. (International Journal of Wrestling Science, 2011)
The purpose of the present investigation was to describe the physical fitness profile of elite cadet wrestlers. Forty-four wrestlers (age: 15.66±0.56 years, weight: 65.75± 16.65 kg and height: 167.8±9.6 cm) who were invited to the national training camps participated in this study. The physical fitness parameters included body weight, maximal oxygen consumption (Bruce protocol), muscular endurance (pull-ups, push-ups, bent-knee sit-ups) and strength (bench press), exclusive power (Standing long jump), speed (40-yd sprint) and agility (4 × 9-m shuttle run). The major results (mean ± SD) are as follows: maximal oxygen consumption (ml·kg-1·min-1): 46.84±3.76; standing long jump (cm): 227.45±20.86; 1-repetition maximum bench press (weight lifted kg in relative to the body weight): 0.88±0.16; push-ups (rep/min): 53.48±10.04; pull-ups (rep): 16.32±8.14; sit-ups (rep/min): 53.41±9.82; speed (s): 6.03±0.46 and agility (s): 9.62±0.65. The present study provides baseline data that have been used in the prescription of individual training programs for these athletes. This information is also available to the coaches and can contribute to the general strategy employed by a wrestler and for a specific match.